Public value management, measurement and reporting - Russo, Salvatore (Emerald, 2014)
This volume aims to shed light on how public service value is identified, managed, measured and reported. The concept of public value has been increasingly associated with the process of modernisation and in recent years the debate has shifted away from 'what' to 'how' public value is conceptualised and practiced. How the public sector can meet the communities' expectations is particularly relevant in light of the Global Financial Crisis. At present, many governments are involved in reform aimed at improving the effectiveness, efficiency and economy of operations, and improving the quality of public services. Examining the effectiveness of these reforms and understanding the gap between the expectations of society and the resources available for public services is an important but under-explored topic. The chapters are the result of a series of conferences and workshops on public value held in 2012 and 2013. There are 20 papers, covering a range of topics, including theoretical reflections, practical case studies and empirical observations aimed at understanding the concept of public value.
Keywords: Political Science -- Public Affairs & Administration.; Public administration.; Public administration -- Evaluation.; Public administration -- Case studies.; Government productivity.; elektronické knihy; electronic books